2015
DOI: 10.1055/s-0035-1554977
|View full text |Cite
|
Sign up to set email alerts
|

Partial Deletion of Chromosome 1p31.1 Including only the Neuronal Growth Regulator 1 Gene in Two Siblings

Abstract: We present two siblings with a partial deletion of chromosome 1p31.1 involving only the neuronal growth regulator 1 (NEGR1) gene. The siblings had a history of neuropsychiatric and behavioral problems, learning difficulties, hypotonia, mild aortic root dilatation, hypermobility, and scoliosis. This is the first clinical report of a microdeletion of chromosome 1p31.1 involving only the NEGR1 gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…For example, gene variants of SynCAMs, which possess three extracellular Ig-like domains as IgLON proteins, have been identified as causal or risk factors for intellectual disability and autism spectrum disorders and SynCAM-deficient mice exhibit social and emotional deficits (Frei and Stoeckli, 2017 ; Gennarini and Furley, 2017 ). More recently, genetic variants in or near the NEGR1 locus have been associated with cognitive disorders including psychiatric disease, intellectual disability and learning difficulties (Veerappa et al, 2013 ; Genovese et al, 2015 ; Tassano et al, 2015 ; Hyde et al, 2016 ). These findings prompted us to examine the brain distribution of NEGR1 mRNA, its role in neurite and axon growth and to provide an initial neuroanatomical and behavioral characterization of Negr1 -KO mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, gene variants of SynCAMs, which possess three extracellular Ig-like domains as IgLON proteins, have been identified as causal or risk factors for intellectual disability and autism spectrum disorders and SynCAM-deficient mice exhibit social and emotional deficits (Frei and Stoeckli, 2017 ; Gennarini and Furley, 2017 ). More recently, genetic variants in or near the NEGR1 locus have been associated with cognitive disorders including psychiatric disease, intellectual disability and learning difficulties (Veerappa et al, 2013 ; Genovese et al, 2015 ; Tassano et al, 2015 ; Hyde et al, 2016 ). These findings prompted us to examine the brain distribution of NEGR1 mRNA, its role in neurite and axon growth and to provide an initial neuroanatomical and behavioral characterization of Negr1 -KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…Gene variants in a regulatory region upstream of the NEGR1 gene have been associated with major depressive disorder (Hyde et al, 2016 ) but also with low white matter integrity (Dennis et al, 2014 ) and intelligence (Sniekers et al, 2017 ). Neuropsychiatric problems and learning difficulties were further reported in two siblings with a mono-allelic microdeletion of chromosome 1p31.1 involving only the NEGR1 gene (Genovese et al, 2015 ). Interestingly, increased cerebrospinal fluid protein levels of NEGR1 were found in major depressive disorder and bipolar disease but not schizophrenia compared to controls (Maccarrone et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, our laboratory has recently demonstrated a role for the immunoglobulin superfamily CAM neuronal growth regulator 1 (NEGR1; Funatsu et al , 1999 ; Schafer et al , 2005 ) in regulating neuronal morphological maturation by a functional interaction with the RTK fibroblast growth factor receptor 2 (FGFR2) through modulation of the FGFR2-ERK signalling pathway in vitro ( Pischedda and Piccoli, 2015 ). Moreover, independent genetic studies have suggested a link among both NEGR1 and FGFR2 and brain disorders, including autism ( Marshall et al , 2008 ; Pinto et al , 2010 ; Hussman et al , 2011 ; Casey et al , 2012 ; Michaelson et al , 2012 ; Neale et al , 2012 ; Genovese et al , 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…A genome-wide copy number scan identified NEGR1 to be one of five new candidate genes involved in dyslexia ( Veerappa et al, 2013 ). A case study on two siblings with interstitial microdeletion of 1p31.1 involving only NEGR1 presented with learning and behavioral problems, hypotonia, hypermobility, scoliosis, and aortic root dilation ( Genovese et al, 2015 ). Further suggestive of the role NEGR1 has in brain disorders, NEGR1 is also elevated in the CSF of bipolar and depressed patients ( Maccarrone et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%